2013
DOI: 10.4172/2329-6917.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Smad and the Mitogen-Activated Protein Kinase Pathways is Essential for Erythroid Differentiation of Erythroleukemia Cells Induced by TGF-β, Activin, Hydroxyurea and Butyrate

Abstract: The role of crosstalk between the Smad and the MAPK signaling pathways in activin-, transforming growth factor-β (TGF-β)-, hydroxyurea (HU) - and butyrate-dependent erythroid differentiation of K562 leukemic cells was studied. Treatment with all four inducers caused transient phosphorylation of Smad2/3 and MAPK proteins including ERK, p38 and JNK. Use of specific inhibitors of p38, ERK and JNK MAPK proteins, and TGF-β type I receptor indicated that differentiation induced by each of these agents involves activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Suppression of Erk1/2 phosphorylation upregulates Smad2/3 phosphorylation and enhances cellular differentiation [32]. These results and those of our study suggest a potential role of Erk1/2 in the activation of PI3K/Akt and suppression of Smad3-dependent signaling in the EndMT of EPCs.…”
Section: Discussionsupporting
confidence: 84%
“…Suppression of Erk1/2 phosphorylation upregulates Smad2/3 phosphorylation and enhances cellular differentiation [32]. These results and those of our study suggest a potential role of Erk1/2 in the activation of PI3K/Akt and suppression of Smad3-dependent signaling in the EndMT of EPCs.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we found that aberrantly expressed miR-150 suppressed the two major signaling pathways involved in erythroblast proliferation and survival, ErbB-MAPK-p38 and ErbB-PI3K-AKT. Activation of the p38 MAPK pathway has been reported to be a prerequisite for inducing erythroid differentiation of K562 cells [ 74 75 ]. TfR1 engagement increased cell sensitivity to EPO to induce erythropoiesis via activating PI3K-AKT pathways [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the TGF-b1 pathway acts through SMADdependent (canonical) and SMAD-independent (non-canonical) pathways [37,38]. Smad2 and Smad3, the principal receptor-activated proteins involved in the TGF-b pathway, are activated directly by TGF-b type I receptor kinase, then translocated to the nucleus complexed with a common co-SMAD, Smad4, to regulate the transcription of target genes [39,40]. Many signaling pathways interact with the TGF-b1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK) cascade, composed mainly of ERK, p38 MAPK and c-Jun N-terminal kinases (JNKs), has been shown to represent a major signaling pathway for TGF-b-dependent SMAD activation [41,42]. In crosstalk between the SMAD and MAPK pathways, TGFb-dependent or -independent induction of activated ERK can occur [40]. We tested crosstalk between the TGF-b/SMAD and ERK pathways in melatonin-induced cell proliferation in our research by transfecting siERK1, siERK2, siS2, siS3 and siS4 into pancreatic progenitor cells treated with melatonin.…”
Section: Discussionmentioning
confidence: 99%